The Effect of Perceived Usefulness, Perceived Ease of Use, and Social Influence on the Use of Mobile Banking through the Mediation of Attitude Toward Use - Denny Indra Prastiawan; Siti Aisjah; Rofiaty Rofiaty (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
Mobile banking is one of the channels of banking service provided by banking institutions in forms of modern platforms that are fully based on digital technology and displace physical interaction between banks and their customers. For banking industry, mobile banking is more than a service option; it is a strategic plan to facilitate customer’s changes in behavior. However, the acceptance of such platform by the public, particularly micro entrepreneurs, is still in question. The objective of this research is to identify factors influencing the use of mobile banking based on the perception of micro customers of Bank DKI in Surabaya. The variables used in this study were developed from previous researches that also examined the same matter with adjustment on the characteristics of micro customers. The variables, developed through the theoretical review, were then empirically assessed using SEM-PLS. the data was collected from questionnaires distributed to 266 micro customers who received financing from Bank DKI. The surcey discovered that perceived usefulness, perceived ease of use, and social influence are empirically proven to have both direct effects on the use of mobile banking and indirect effects through attitude toward use. Practical implications also discussed in this paper.